Barsilowsky's Base and Perkin's Base: Two Products from the Oxidation of P-Toluidine. (June 2014) - Plater, M. John; Harrison, William T.A.
The oxidation of p -toluidine in H + /H2 O can give mainly a tetramer, a trimer, or a mixture of both. The outcome is dependent upon the oxidant, the pH and the concentration of p -toluidine. Both the trimer and tetramer are definitively characterised by X-ray single crystal structure determination.